Trademark image retrieval using weighted combination of sift and HSV correlogram. (2016) - Nigam, Akriti; Tripathi, R.C.
This paper describes an effective tool to automate the process of trademark similarity checking at the time of registration. A combination of shape and colour feature has been illustrated here so that images taken from different vantage points or levels fall into the same group. This was particularly important for trademark images to curb attempts at trademark infringement through object transformations. SIFT has been used as a powerful technique that is unaffected by various transformations like rotation, scaling, translation, change in view etc. Correlogram on the other hand has been used to describe the colour content of the image which is then combined with SIFT to completely represent a trademark image.